Impact of mindfulness in Islamic Law: Applied study - Alkandari, Mariam Ahmad (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: The study aims to elucidate the concept of mindfulness, its importance and jurisprudential ruling in Islamic law, and its effects and applications on acts of worship. Methods: the study used the extrapolatory and analytical approach: by following the reliable research materials related to mindfulness through collection, analysis and distribution to each part of the study. It also utilzed the deductive approach to discern how to activate mindfulness upon performing acts of worship. Results: The study concluded that the concept of mindfulness - that indicates the necessity of focusing on the present moment while preserving the mind from distractions - is of a great importance in Islamic law. Mindfulness helps Muslims enhance the sense of Watchfulness by Allah the Almighty and trust in Him when worshiping and supplicating Him, and keeping devotion to Him in all circumstances and dealings. Moreover, the study seeks to explain the impact of mindfulness on the submissiveness of Muslims while praying, and highlights its role in instilling ethical values, achieving sustainable economic development and protecting the environment, besides its impact on fostering meditation and reflection of Qur’an in reading and listening to it. Conclusions: Mindfulness is crucial to deepening religious awareness for Muslims and enhancing their belief in Allah’s omnipresence and support to His servants in all their dealings. In worshiping Allah, awareness of the heart and alertness of the mind are among the reasons for accepting deeds, gaining Allah’s Pleasure, and reaching His Paradise.